Cardiovascular Risk Factor Control and Lifestyle Factors in Young to Middle-Aged Adults with Newly Diagnosed Obstructive Coronary Artery Disease - Garshick, Michael S. (Cardiology, 2019)
BACKGROUND: While progress in the prevention of cardiovascular disease (CVD) has been noted over the past several decades, there are still those who develop CVD earlier in life than others. OBJECTIVE: We investigated traditional and lifestyle CVD risk factors in young to middle-aged patients compared to older ones with obstructive coronary artery disease (CAD). METHODS: A retrospective analysis of patients with a new diagnosis of obstructive CAD undergoing coronary intervention was performed. Young to middle-aged patients were defined as those in the youngest quartile (n = 281, mean age 50 ± 6 years, 81% male) compared to the other three older quartiles combined (n = 799, mean age 69 ± 7.5 years, 71% male). Obstructive CAD was determined by angiography. RESULTS: Young to middle-aged patients compared to older ones were more likely to be male (p < 0.01), smokers (21 vs. 9%, p < 0.001), and have a higher body mass index (31 ± 6 vs. 29 ± 6 kg/m(2), p < 0.001). Younger patients were less likely to eat fruits, vegetables, and fish and had fewer controlled CVD risk factors (2.7 ± 1.2 vs. 3.0 ± 1.0, p < 0.001). Compared to older patients, higher levels of psychological stress (aOR 1.6, 95% CI 1.1–2.4), financial stress (aOR 1.8, 95% CI 1.3–2.5), and low functional capacity (aOR 3.3, 95% CI 2.4–4.5) were noted in the young to middle-aged population as well. CONCLUSION: Lifestyle in addition to traditional CVD risk factors should be taken into account when evaluating risk for development of CVD in a younger population.